2022
DOI: 10.1097/jsm.0000000000001077
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the International Olympic Committee Sport Mental Health Assessment Tool 1: Screening for Mental Health Symptoms in a Canadian Multisport University Program

Abstract: Objective: To apply the International Olympic Committee Sport Mental Health Assessment Tool 1 (SMHAT-1) to determine the prevalence of mental health symptoms in a cohort of university student athletes over an academic year. A secondary objective was to explore the internal consistency of the screening tools from the SMHAT-1. Design: Cross-sectional design with 3 repeated measurements over an academic year. Setting: A large university multisport program. Participants: Five hundred forty-two university-level stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 27 publications
(35 reference statements)
2
18
3
Order By: Relevance
“…In our sample, female athletes tended to score higher on the APSQ, GAD-7 and PHQ-9 compared with male athletes, consistent with previous findings 12 14–17. Some preliminary data also suggest that Paralympic and Winter sport athletes experience a greater degree of psychological distress,17 which supports our observation of greater scores on the APSQ and other subscales compared with the Olympic and Summer sport counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…In our sample, female athletes tended to score higher on the APSQ, GAD-7 and PHQ-9 compared with male athletes, consistent with previous findings 12 14–17. Some preliminary data also suggest that Paralympic and Winter sport athletes experience a greater degree of psychological distress,17 which supports our observation of greater scores on the APSQ and other subscales compared with the Olympic and Summer sport counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…This prevalence is slightly higher compared to the Australian professional soccer players (up to 62.9%) [47], professional golfers (51.7%) [48], and active and former elite athletes (57.1%) who participated in the IOC survey [18]. Depending on the subject's background and the timing of the screening implementation, the prevalence of psychological distress varies widely; another report on Canadian student-athletes showed different APSQ positive rates at three-time points, ranging from 24.3 to 39.6% [19]. This study presented the reference values for the prevalence of each mental health symptom using the Japanese version of SMHAT-1.…”
Section: Discussionmentioning
confidence: 99%
“…While the SMHAT-1 is used broadly and disseminated gradually in research and practice, the feasibility of the SMHAT-1 and how to apply it in sports are under study across the globe. A study from a sample of Canadian university-level student-athletes [19] showed it to be feasible to implement with good internal consistency. In addition, a recent study by Taylor and colleagues [20] indicated that the SMHAT-1 were generally a reliable screening tool for mental health symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…This supplement focuses on cisgender female athletes (assigned female at birth) due to the sex-specific health issues outlined. We also acknowledge mental health and the gendered sports environment, which may influence injury risk12 and health outcomes 13 14. These are not unique to cisgender female athletes, but are more prevalent than in cisgender male athletes 14.…”
Section: Scope Of This Supplementmentioning
confidence: 99%
“…We also acknowledge mental health and the gendered sports environment, which may influence injury risk12 and health outcomes 13 14. These are not unique to cisgender female athletes, but are more prevalent than in cisgender male athletes 14. Additionally, women and girls with variations of sex development, transgender women and girls and gender diverse athletes may experience some of the same health concerns and gendered experiences as cisgender female athletes.…”
Section: Scope Of This Supplementmentioning
confidence: 99%